PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA PEMILIK MOBIL TOYOTA DI KOTA MEDAN) - risa angela marisi b nainggolan; Marhayanie Marhayanie Marhayanie (Jurnal Media Informasi Manajemen, 2013)
ABSTRACT   This study aims to determine the influence of brand equity (brand awareness, brand association, perceived quality, and brand loyalty)  to the purchasing decision of the owners of Toyota’s car in Medan, and which variables among the variables of brand awareness, brand association, perceived quality, and brand loyalty are the most dominant in influencing the purchasing decision of Toyota’s car owners in Medan. The study was conducted to the owners of Toyota’s car in Medan. The population in this study are all customers/owners of Toyota’s car in Medan. The number of sample can be obtained by using the formula for population whose number is unknown. Sampling technique uses an incidental sampling method. This research is descriptive and verificative research, and using primary and secondary data which is obtained by questionnaires and doing the study of documentation using Likert scale. The analysis method which is used is descriptive analysis method and the multiple regression analysis method. The results of this study indicate that simultaneously brand awareness, brand association, perceived quality, and brand loyalty has a positive and significant impact on purchasing decisions of the Toyota’s car owners in Medan. Brand loyalty can be seen as the most dominant variable in influencing the purchasing decision of Toyota’s car owners in Medan. Adjusted R Square = 0,650, this means 65% of purchasing decision factors can be explained by the independent variables (brand awareness, brand association, perceived quality, and brand loyalty), while the 35% remaining is explained by other factors which is not examined in this study. Keywords:       Brand Equity, Brand Awareness, Brand Association, Perceived Quality, Brand Loyalty, and Purchasing Decisions.